(3Yjhf GdJaSjQ ddaVdGA GdSeGSjQs - (3GdSjhGSj, CMeO Hf eMehO TgGH GdOjf, J (B803 (3g`s ((3MHjH Hf eDefs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj CfRd GdbQBf cdGeG bjeG aGdJCLJ Edi Gddg GdhgGH Cf CfJNH ef Jdc GdJaGSjQ JaSjQG eNJUQG hSejJg Yjhe GdJaGSjQ ddaVdGA GdSeGSjQ s
(3BNQgG (B:s
(3abGd Udi Gddg Ydjg hSde (B: (3GbQC BNQ Hfj ESQGFjd (B[ (3bd GOYhG Gddg (B] (3MJi JNJe Ke bd JhcdJ Ydi GdMj GdPj dG jehJ KdGK eQGJ (B, (3hgPg GdBjI JSei BjI GdYRI hcGf GdfHj Udi Gddg Ydjg hSde jYdegG GdUZjQ EPG aUM ef Hfj YHO GdeWdHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 254s
(3eYLe GdeDdajf (B1 / 305s
(3cTa GdXfhf (B2 / 1185s
(3gOjI GdYGQajf (B1 / 118s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs